Frequency of the association of metabolic syndrome in patients with liver cirrhosis hospitalized for variceal hemorrhage at Hospital Juárez de México - T Deaquino Reyes; F Sánchez Salinas; C Mendoza Sangeado; S Mejía Loza (Annals of Hepatology, 2022)
Introduction and Objectives: Clinical studies show a high prevalence of components of the metabolic syndrome (MS) in patients with liver cirrhosis not associated with NAFLD as a factor that increases portal hypertension (PH) and the frequency of variceal hemorrhage. This study aimed to determine the frequency of variceal hemorrhage among hospitalized patients with non-NAFLD liver cirrhosis who meet the criteria for MS and patients without MS in the Gastroenterology Service of the HJM from January to April 2022. Materials and Methods: Comparative, descriptive, retrospective and cross-sectional study of a cohort of patients with liver cirrhosis hospitalized for variceal hemorrhage. Forty files were reviewed, excluding those with NAFLD etiology, divided into group A with MS and group B without MS.Results. Of the sample (n=40), 70% were men and 30% were women. Results: Table 1. characteristics of patients with variceal hemorrhage with and without metabolic syndrome Conclusions: Despite the small number of patients, it is observed that MS, diabetes mellitus and arterial hypertension are independent factors for the development and evolution of PH, so they should be considered in the primary and secondary prevention of variceal hemorrhage. Funding: The resources used in this study were from the hospital without any additional financing Declaration of interest: The authors declare no potential conflicts of interest.